Long-term experience with percutaneous biopsies of pelvic lesions using CT guidance - Hoffmann, Petr; Balik, Michal; Hoffmannova, Martina; Spacek, Jiri; Vanasek, Jiri; Rezac, Adam; Dvorak, Petr (Science progress, 2021)
To evaluate the accuracy, efficiency, complication rate, technical features, and relations among followed parameters of CT-guided percutaneous biopsies of the pelvic lesions. 140 biopsies in 136 patients for tumors, sizes 17-160 mm in largest diameter, were carried out in patients with probable tumorous pelvic process within ten years period. The patients were women in 77 cases and men in 59 cases, aged 21 to 87 years. The lesionsÂ´ size varied from 17 mm to 160 mm in largest diameter. In 135 biopsies (96.4%) results were true positive or true negative; only 5 procedures (3.6%) were histologically false negative and had to be verified surgically. Metastatic affection was the most common diagnosis (26.4%). Lymphomas were diagnosed in 25%; serous adenocarcinoma of ovary or uterine tube was verified in 15.7% of cases. Totally 7 complications (5%) were confirmed, all were minor hemorrhages. A statistically significant relation between the complication rate and hypervascular character (p = 0.00004), and between needle gauge and histological accuracy (p = 0.00429) was revealed. Core needle biopsy using percutaneous approach and CT guidance had a high overall accuracy in determining the final histological diagnosis including subtyping. Concurrently, the complication incidence was low.
Keywords: počítačová rentgenová tomografie; ultrazvukem navigovaná biopsie; Humans; Pelvic tumor; biopsie dutou jehlou; Pelvis; Female; CT guidance; Image-Guided Biopsy; lidé; pánev; ženské pohlaví; Male; Retrospective Studies; Tomography, X-Ray Computed; complication rate; retrospektivní studie; mužské pohlaví; diagnostic accuracy; core needle biopsy; percutaneous approach; Biopsy, Large-Core Needle